Global Proteomic Analysis of Two Tick-Borne Emerging Zoonotic Agents: Anaplasma Phagocytophilum and Ehrlichia Chaffeensis - Lin, Mingqun; Kikuchi, Takane; Brewer, Heather M.; Norbeck, Angela D.; Rikihisa, Yasuko (Frontiers in Microbiology, 2011)
Anaplasma phagocytophilum and Ehrlichia chaffeensis are obligatory intracellular alpha-proteobacteria that infect human leukocytes and cause potentially fatal emerging zoonoses. In the present study, we determined global protein expression profiles of these bacteria cultured in the human promyelocytic leukemia cell line, HL-60. Mass spectrometric (MS) analyses identified a total of 1,212 A. phagocytophilum and 1,021 E. chaffeensis proteins, representing 89.3% and 92.3% of the predicted bacterial proteomes, respectively. Nearly all bacterial proteins (≥ 99%) with known functions were expressed, whereas only approximately 80% of “hypothetical” proteins were detected in infected human cells. Quantitative MS/MS analyses indicated that highly-expressed proteins in both bacteria included chaperones, enzymes involved in biosynthesis and metabolism, and outer membrane proteins, such as A. phagocytophilum P44 and E. chaffeensis P28/OMP-1. Among 113 A. phagocytophilum p44 paralogous genes, 110 of them were expressed and 88 of them were encoded by pseudogenes. In addition, bacterial infection of HL-60 cells up-regulated the expression of human proteins involved mostly in cytoskeleton components, vesicular trafficking, cell signaling, and energy metabolism, but down-regulated some pattern recognition receptors involved in innate immunity. Our proteomics data represent a comprehensive analysis of A. phagocytophilum and E. chaffeensis proteomes, and provide a quantitative view of human host protein expression profiles regulated by bacterial infection. The availability of these proteomic data will provide new insights into biology and pathogenesis of these obligatory intracellular pathogens.